Study on the interpretation and application of the concept of “effective control” by the ISA - Zhou, Jiang; Lin, Ping (Frontiers in Marine Science, 2024)
The United Nations Convention on the Law of the Sea (UNCLOS) include the term of "effective control" in its sponsorship provisions but do not clarify its meaning. To arrive at a consensus on its connotation, the International Seabed Authority (ISA) began discussions on the concept of "effective control" that have been ongoing since 2014 but have still not yielded any definite conclusion. The interpretation and application of this concept tend to be construed as a regulatory standard in current discussion documents and practices of the ISA, where this allow contractors from developed countries to easily use the method of "sponsoring states of convenience" to apply for and obtain contracts to reserved areas. This is inimical to the goals of effective marine environmental protection and the implementation of preferential treatment for developing countries. The international community should pay attention to this issue and correct the unreasonable tendencies of the ISA in this regard.